Nuclear magnetic resonance imaging of the heart. Current status and future prospects. - Steiner, R E (1983)
The basic principles and current status of proton nuclear magnetic resonance imaging are outlined. Nuclear magnetic resonance images of the heart have improved in quality with advances in technique and better gating but clinical experience remains very limited. Myocardial infarction has been shown in animals and man, and plaques of atheroma have been seen with nuclear magnetic resonance flow studies. Further improvements in image quality, faster examination times, 23Na imaging, and the use of paramagnetic contrast agents are advances that are anticipated in the near future.